Multi-sensory design - Creating healthier public spaces - Turner, B (UKCIP, 2017)
The design of the built environment can have a profound impact on perception, place identity and place experience. On behalf of the Adaptation and Resilience in the Context of Change (ARCC) network and the Revealing Spaces workgroup of the Feeling Good Foundation, we ran a series of events focused on the senses, to encourage reflection on the consequences of public realm design on city dwellers' physical, emotional and psychological wellbeing.